Comparison of Tranexamic Acid Versus Placebo for Prevention of Postpartum Hemorrhage in Females Undergoing Delivery at Term (Medical Forum Monthly, 2024)
Objective: The objective of the present study was to compare the mean blood loss with intravenous tranexamic acid versus placebo in pregnant females presenting at term for delivery.Study Design: Randomized control trial study.Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology, Saidu group of Hospital, Swat, from January 2023 to June 2023.Methods: Through non-probability consecutive sampling, a Sample size of 250 women (Group A- TXA group n=125, Group B- Placebo n=125). In group A, females were given intravenous tranexamic acid. In group B, females were given an injection of normal saline. All females were followed till delivery. After delivery, the female was shifted to the ward and blood loss was measured.Results: Mean± S. D of the pre-operative hemoglobin (HB) of the participants in groups A and B was 11.99 ± 0.72 and 12.44 ± 0.86 g/dL, respectively (P<0.0001). Mean± S. D of the post-operative hemoglobin (HB) of the participants in groups A and B was 10.8 ± 0.73 and 7.44 ± 0.976 g/dL, respectively (P<0.0001). Mean± S. D of the blood loss of the participants in groups A and B was 297.56 ± 69.4 and 912.10 ± 67.1mL, respectively (P<0.0001). In group A, 17% of participants had blood loss of more than 1000mL, while in group B 50% of participants had blood loss of more than 1000mL (p<0.0001). In group A, 8% of participants required a blood transfusion, while in group B 26% of participants required a blood transfusion (p<0.0001).Conclusion: The research emphasized the importance of tranexamic acid in the management of post-partum hemorrhages, the enhancement of post-partum hemoglobin levels, and the potential reduction in the need for blood transfusions.